Struggling with God : Kierkegaard and the temptation of spiritual trial - Podmore, Simon D., 1977- (Cambridge : James Clark & Company, 2013)
Invoking the biblical motif of Jacob's struggle with the Face of God (Genesis 32), Simon D. Podmore undertakes a constructive theological account of 'spiritual trial' (tentatio; known in German mystical and Lutheran tradition as Anfechtung) in relation to enduring questions of the otherness and hiddenness of God and the self, the problem of suffering and evil, the freedom of Spirit, and the anxious relationship between temptation and ordeal, fear and desire. This book traces a genealogy of spiritual trial from medieval German mystical theology, through Lutheran and Pietistic thought (Tauler; L.
Struggling with God : towards a Kierkegaardian theology of spiritual trial -- The secret struggle : lost in translation -- The old devotional books : Anfechtung in Tauler and the Theologia Deutsch -- Melancholia coram Deo : Luther's theology of Anfechtung -- God's fire in the soul : Anfechtung in Arndt and Boehme -- Before God in secret : spiritual trial and temptation in Kierkegaard I -- The God-forsaken God : spiritual trial and temptation in Kierkegaard II -- The desire of spirit : restlessness and the transparency of rest -- The temptation of spiritual trial.
Includes bibliographical references.
Online resource; title from PDF title page (ebrary, viewed November 29, 2013).
Master record variable field(s) change: 072
Keywords: Christianity -- Philosophy; Philosophy and religion; RELIGION -- Philosophy; Existentialism; Philosophy and religion; Theology; Religion; RELIGION / Christian Life / Spiritual Warfare; Electronic books